Delayed Harvest Reduces Postharvest Quality and Storability of Southern Highbush cv. Meadowlark and Rabbiteye Blueberry cv. Brightwell - Amit Godara; Zilfina Rubio Ames; Angelos Deltsidis (HortScience)
Blueberries are produced worldwide due to their high demand and antioxidant benefits. Berry quality, including texture, flavor, and antioxidant properties, influence consumer preferences and marketability. Harvesting blueberries at shorter intervals is essential for maintaining fruit quality, including firmness and flavor, while also minimizing postharvest losses. This study investigated the effects of delayed harvests on the postharvest quality of ‘Meadowlark’, a highbush blueberry, and ‘Brightwell’, a rabbiteye blueberry, harvested from two different locations in South Georgia in 2022 and 2023. The treatments consisted of harvest dates, with two harvests in 2022 and three harvests in 2023, followed by three storage-duration treatments (7, 14, and 21 days of storage) to evaluate postharvest quality. Fruit firmness, berry diameter, color, total soluble solids, titratable acidity, berry damage (%), and anthocyanin concentration were assessed at harvest and following storage days. In both cultivars, harvest 1 showed higher fruit firmness and storability compared with harvests 2 and 3 in 2023. During storage, the decline in firmness was higher in harvests 2 and 3 compared with harvest 1. Fruit from the delayed harvests exhibited the highest percentage of berry damage both at harvest and after 21 days of storage. Anthocyanin concentration varied across cultivars and years, with berries from harvest 2 having a higher anthocyanin concentration at harvest in 2022 and 2023 in the Brightwell cultivar. Overall, this study highlights the importance of optimizing harvest dates to maintain the postharvest quality and shelf life of blueberries.